2016
DOI: 10.1016/j.ecolind.2015.08.034
|View full text |Cite
|
Sign up to set email alerts
|

Uncertainty and sensitivity analysis of West Java Water Sustainability Index – A case study on Citarum catchment in Indonesia

Abstract: Water sustainability indices have been recently used to measure the sustainability of water resources within a catchment. Developing a sustainability index involves various steps, some of which have uncertainties associated with them. For the recently developed West Java Water Sustainability Index (WJWSI), three sources of uncertainties were identified, namely uncertainties in the thresholds of noncategorical indicators and sub-indicators, in the weighting schemes, and in the aggregation methods. This paper pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(17 citation statements)
references
References 21 publications
0
17
0
Order By: Relevance
“…In everyday life humans are also not separated from to meet their daily needs, such as eating, drinking, washing and others. Therefore, it is of utmost importance to maintain the sustainability of water resources, so that these resources can be utilized by humans and others, now and also in the future [22]. The world is currently faced with SDGs (Sustainable Development Program).…”
Section: Discussionmentioning
confidence: 99%
“…In everyday life humans are also not separated from to meet their daily needs, such as eating, drinking, washing and others. Therefore, it is of utmost importance to maintain the sustainability of water resources, so that these resources can be utilized by humans and others, now and also in the future [22]. The world is currently faced with SDGs (Sustainable Development Program).…”
Section: Discussionmentioning
confidence: 99%
“…Because of this advantage of the geometric aggregation method over the other aggregation methods, this method was used to aggregate the WJWSI indicators and sub-indicators . As far as the weighting is concerned, the uncertainty and sensitivity analysis of WJWSI (Juwana et al, 2016) showed that either equal or non-equal weighting scheme can be used for future use of WJWSI, since changes from equal to non-equal weighting scheme did not significantly affect the final index. Thus, the application of WJWSI to the three catchments presented in this study uses the equal weighting scheme.…”
Section: Aggregation Of Sub-index Valuesmentioning
confidence: 99%
“…= 558,427 1 + 558,427 0.08 2 = 156 respondents Sugiyono [13][14][15][16] stated that Slovin formula allows the maximum of 10 % error threshold. Thus, the use of 8 % in this study for the error is justified.…”
Section: Number Of Respondentsmentioning
confidence: 99%